A Road Map for the Global Elimination of Congenital Syphilis. (14th July 2010) - Kamb, Mary L.; Newman, Lori M.; Riley, Patricia L.; Mark, Jennifer; Hawkes, Sarah J.; Malik, Tasneem; Broutet, Nathalie
Abstract : Congenital syphilis is the oldest recognized congenital infection, and continues to account for extensive global perinatal morbidity and mortality today. Serious adverse pregnancy outcomes caused by maternal syphilis infection are prevented with screening early in pregnancy and prompt treatment of women testing positive. Intramuscular penicillin, an inexpensive antibiotic on the essential medicine list of nations all over the world, effectively cures infection and prevents congenital syphilis. In fact, at a cost of $ 11–15 per disability adjusted life year (DALY) averted, maternal syphilis screening and treatment is among the most cost-effective public health interventions in existence. Yet implementation of this basic public health intervention is sporadic in countries with highest congenital syphilis burden. We discuss the global burden of this devastating disease, current progress and ongoing challenges for its elimination in countries with highest prevalence, and next steps in ensuring a world free of preventable perinatal deaths caused by syphilis.